The write-brain workbook : 382 exercises to free your creative writing - Neubauer, Bonnie, frey50 (Cinncinati, OH Writer's Digest Books, 2015)
Banish the blank page! Full of 400 stimulating writing prompts, you will create quirky characters, discover fresh twists on classic word games, sample new forms and generate scores of ideas for poems, short stories, articles and even novels.
Keywords: Writing - Exercises